Developing an aqueous approach for synthesizing Au and M@Au (M = Pd, CuPt) hybrid nanostars with plasmonic properties. Issue 2 (25th November 2014) - Du, Jingshan; Yu, Junjie; Xiong, Yalin; Lin, Zhuoqing; Zhang, Hui; Yang, Deren
Abstract : A general route for controllably synthesizing Au-based nanostars was developed in an aqueous solution containing CTAB and ethanolamine. Abstract : Anisotropic Au nanoparticles show unique localized surface plasmon resonance (LSPR) properties, which make them attractive in optical, sensing, and biomedical applications. In this contribution, we report a general and facile strategy towards aqueous synthesis of Au and M@Au (M = Pd, CuPt) hybrid nanostars by reducing HAuCl4 with ethanolamine in the presence of cetyltrimethylammonium bromide (CTAB). According to electron microscopic observations and spectral monitoring, we found that the layered epitaxial growth mode ( i.e., the Frank-van der Merwe mechanism) contributes to the enlargement of the core, while the random attachment of Au nanoclusters onto the cores accounts for the formation of the branches. Both of them are indispensable to the formation of the nanostars. The LSPR properties of the Au nanoparticles have been well investigated with morphology control via the precursor amount and growth temperature. The Au nanostars showed improved surface-enhanced Raman spectroscopy (SERS) performance for rhodamine 6G due to their sharp edges and tips, which were therefore confirmed as good SERS substrates to detect trace amounts of molecules.